Acoustic analysis of swallowing as an auxiliary method for assessing dysphagia in Parkinson's disease - Silva, Glauce (2022)
Objective: To measure the accuracy of DeglutiSom as an auxiliary method to assess swallowing in patients with Parkinson's disease (PD). Methodology: Accuracy study. Among 248 individuals, 91 participants met the inclusion criteria, with a mean age of 64.9 years (SD 7.7), 53.8% male and 46.2% female, with a mean disease duration of 12.6 years (SD 3.8 years). Two instrumental studies were performed: An acoustic analysis with Sonar Doppler via the DeglutiSom Software, and a videofluoroscopic swallow study. Three judges analyzed the swallowing sounds in the DeglutiSom software and the instrumental examination findings. Results: The inter-rater reliability was 90.1%, with 4.4% degree of partial agreement and 5.5% disagreement. Sensitivity resulted in 90.0% and specificity in 90.0%. A sensitivity of 97.0% and specificity of 91.0% are indicators of a high validity for the dysphagia screening method, with predictive value (+) of 97.0% and predictive value (-) of 91.0%, with an accuracy method of 96.0%. The validity indicator values for screening aspiration were also high, with a sensitivity of 90.0%, specificity of 90.0%, predictive value (+) of 82.0%, predictive value (-) of 95% , 0% and 90.0% accuracy. Conclusion: The method proposed is considered appropriate for oropharyngeal dysphagia and tracheal aspiration screening in patients with Parkinson's Disease.